Koncepcja człowieka a pozytywny porządek świata - Stępniak, ks. Marek (Annales. Etyka w Życiu Gospodarczym, 2012)
Looking at the modern events shouldn't we claim that it is impossible to create the positive order of the world there where the human souls are running wild? This strict but at the same time full of realism statement of the Head of the Catholic Church taken from the encyclical on the Christian hope has often appeared in the social teaching of the Church in the recent years, it is repeated in a different form during the Benedict XVI's meetings with the high and mighty of this world and the faithful. This „decline of the souls” is the first reason for the economic crisis. It is a challenge which must be faced by the goodwill people. The rejection of the natural law and the God's law expressed in the Decalogue does not make a human being happier but it introduces divisions, social conflicts and the exploitation. Therefore, the moral revival of people and societies, the respect for human dignity and people's natural rights must go hand in hand with the wise political and economic activities in order to solve the modern „social issue”. Without the moral revival, all other solutions, which can be expected looking for example, at the Polish political scene after the last election, sooner or later will turn against the human being and will cause the irretrievable social damage.